电机轴滚花过盈配合数值模拟与试验研究 - 赵俊杰; 鲁寨军; 谢素超 (Jixie chuandong)
A method of knurl press fit for motor shaft rigidity connection is researched through numerical simulation and test research.The 3 dimensional assemble model of shaft with knurl press fit is built and the numerical simulation model is built through the finite element method.The press in process is researched deeply and the verification test is carried out.By comparing the simulated analysis result and test result,the effectiveness of simulation model is verified,then the relationship between interference value of press fit and max transferred torque moment is researched.An effective way to research knurl press fit is provided by this method.